Pengembangan Media Pembelajaran Berbasis TI pada Materi Penyajian Data Kelas VII untuk Meningkatkan Hasil Belajar - Dinar Dwi Yuliyanti; Arika Indah Kristiana; Lioni Anka Monalisa (jcgant, 2021)
The development of technology has a very big influence in various fields of human life, especially in the field of education. One of its uses is as a tool in the learning process. Technology-based learning can make learning more interesting, effective and efficient, so that students are more enthusiastic about learning and easy to understand the material presented. The model used is the Thiagarajan or 4-D model which consists of four stages, namely the define, design, develop, and dissenimante stages. There are three data collection techniques carried out in this study, namely validity, obtained through validation by the validator; practicality, obtained from media user response questionnaires by students; effectiveness, obtained through the results of student learning tests after using the media. The results showed that the correlation coefficient with a valid interpretation was very high at 0.94. The results of the media user response questionnaire with a percentage of 88.25%. The results of the learning test with a percentage of completeness reaching 85.18% indicate that the learning media can be categorized as effective.